2007
DOI: 10.1590/s0102-311x2007000600024
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis infection: risk factors for children living in sub-standard settlements in Brazil

Abstract: The objective of the present study was to characterize Giardia duodenalis infection among children living in sub-standard settlement areas in the municipality of Juiz de Fora, Minas Gerais State, Brazil. The cross-sectional epidemiological study included 590 children from 1 to 5 years of age. Data were collected from one child per selected family through home interviews with the parent or guardian and parasitological examination of stool samples. Thirty-one putative risk factors concerning family structure, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 8 publications
2
17
0
16
Order By: Relevance
“…infections (lasting ! 14 days) in studies in Brazil of urban preschool children 54 or peri-urban children < 1-12 years of age (mean age ¼ 3.4 years). 40 Chronic infection and diarrhea were also higher in children with poor hygiene and from households with low water quality.…”
Section: Discussionmentioning
confidence: 99%
“…infections (lasting ! 14 days) in studies in Brazil of urban preschool children 54 or peri-urban children < 1-12 years of age (mean age ¼ 3.4 years). 40 Chronic infection and diarrhea were also higher in children with poor hygiene and from households with low water quality.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of 51.8% found for G. duodenalis was higher than that found in previous studies conducted in several regions in Brazil, which reported positivity of 8-29%. 16,17 According to Thompson,2 the high prevalence at daycare centers suggests an infection pattern similar to that of enteric bacterial infections, which are introduced by a single child, spread rapidly, remain in the environment and serve as a source of future infections. Worldwide prevalence studies indicate that the parasite is cosmopolitan, reaching rates of 2-5% in industrialized countries and 20-30% in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Outro fator importante é o uso indiscriminado de antiparasitários, já que tem sido relatado que pacientes previamente tratados com anti-helmínticos, em dose única, apresentaram redução nas infecções por A. lumbricoides e T. trichiura, porém elevação da infecção por G. lamblia 24 . A prevalência verificada no presente estudo foi semelhante àquelas encontradas em outros trabalhos realizados com diferentes amostras da população brasileira de baixa condição socioeconômica [25][26][27] . Apesar de a área de estudo ser endêmica para geo-helmintíases, neste estudo não houve interferência de coinfecções ativas por helmintos.…”
Section: Discussionunclassified